2012
DOI: 10.1007/s00296-012-2522-1
|View full text |Cite
|
Sign up to set email alerts
|

Is the prevalence of arterial hypertension in rheumatoid arthritis and osteoarthritis associated with disease?

Abstract: Objective. In this study, we compare the prevalence of HT in RA and OA patients, exposed to high-and low-grade chronic inflammation, respectively , to assess the possible association between chronic inflammation and HT. Methods.A total of consecutive 627 RA and 352 OA patients were enrolled in this multicentric study. HT was defined as a systolic blood pressure (BP) ≥140 and/or diastolic BP ≥90 mmHg or current use of any antihypertensive drug. Overweight/obesity was defined as body mass index (BMI) ≥25, and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…Self-reported arthritis was an independent risk factor for hypertension in this study. As shown in other studies, arthritis is associated with hypertension since both diseases have common risk factors including aging [ 56 ]. Research also indicates metabolic syndrome and aging-related phenotypes for osteoarthritis, which explains the link between all three conditions in our study [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 73%
“…Self-reported arthritis was an independent risk factor for hypertension in this study. As shown in other studies, arthritis is associated with hypertension since both diseases have common risk factors including aging [ 56 ]. Research also indicates metabolic syndrome and aging-related phenotypes for osteoarthritis, which explains the link between all three conditions in our study [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 73%
“…In a cross-sectional study in 2013, Morovic-Vergles et al [19], found that among 352 patients with OA, 60% had hypertension after adjusting for age and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that there may be several shared risk factors implicated in the plausible mechanisms of the relationship between hypertension and knee OA. [ 41 , 42 ] One possible explanation for the relationship between hypertension and knee OA is shared traditional risk factors, such as aging, obesity, and chronic inflammation. [ 2 , 9 , 43 , 44 ] Moreover, some studies have proven that multiple genes are involved in both hypertension and knee OA.…”
Section: Discussionmentioning
confidence: 99%